2020
DOI: 10.1108/ejm-02-2019-0145
|View full text |Cite
|
Sign up to set email alerts
|

Close knit: using consumption communities to overcome loneliness

Abstract: Purpose This paper aims to highlight the role of consumption communities as a self-help support group to ameliorate loneliness. The authors suggest that the self-help element of consumption communities has been overlooked because of a focus on communities pursuing hegemonic masculinity. Instead, the authors focus on a female-led and – dominated consumption community. Design/methodology/approach A longitudinal ethnography was undertaken with the aim of understanding consumer behaviour in a “hyper-feminine” en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 95 publications
1
17
0
Order By: Relevance
“…Literature in this regard has shown that consumers develop meaningful relationships with the brands, consumption communities, service providers and in-store salespersons that buffer interpersonal insecurity and compensate consumers’ fundamental need for belongingness [ 1 , 57 , 59 ]. For example, Snyder and Newman [ 57 ] showed that consumers treat brand communities as a viable avenue for social connections.…”
Section: Lonely Consumers: Psychological Commercial and Social Immentioning
confidence: 99%
See 4 more Smart Citations
“…Literature in this regard has shown that consumers develop meaningful relationships with the brands, consumption communities, service providers and in-store salespersons that buffer interpersonal insecurity and compensate consumers’ fundamental need for belongingness [ 1 , 57 , 59 ]. For example, Snyder and Newman [ 57 ] showed that consumers treat brand communities as a viable avenue for social connections.…”
Section: Lonely Consumers: Psychological Commercial and Social Immentioning
confidence: 99%
“…For example, Snyder and Newman [ 57 ] showed that consumers treat brand communities as a viable avenue for social connections. The traditional communities, which are geographically-bound, are in decline in the fragmented modern society, whereas the brand communities are fast-growing on social media, which create social relatedness and ease loneliness [ 1 ]. In an offline setting, Smith, Rippé and Dubinsky [ 4 ] and Rippé, Smith and Dubinsky [ 5 ] investigated how the lonely consumers ‘befriend’ the in-store salespersons to cope with perceived deficiencies of social relationships.…”
Section: Lonely Consumers: Psychological Commercial and Social Immentioning
confidence: 99%
See 3 more Smart Citations